2021
DOI: 10.1021/acssuschemeng.1c06514
|View full text |Cite
|
Sign up to set email alerts
|

Anchoring of Ni12P5 Microbricks in Nitrogen- and Phosphorus-Enriched Carbon Frameworks: Engineering Bifunctional Active Sites for Efficient Water-Splitting Systems

Abstract: The demand for developing high-efficiency multifunctional electrocatalysts with a long-term stability rapidly increases for achieving the commercialization of sustainable hydrogen (H 2 ) production via cost-effective water electrolysis systems. This study describes single-phase metal-rich nickel phosphide (Ni 12 P 5 )-incorporated carbon composites for a highly efficient water-splitting system. The distinct Ni 12 P 5 is anchored in nitrogen (N)-and phosphorus (P)-rich carbon matrices (Ni 12 P 5 @N,P-C); the cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 89 publications
0
14
0
Order By: Relevance
“…This demonstrated that the Ni site exerted electron donor properties and the metal Ni could act as a bridge for electron transfer between Ni 3 P and VN. Additionally, from the P 2p spectrum presented in Figure 3d, the P 2p of Ni 3 P/Ni/VN@NC could be distinguished by the featured peaks located at 128.48 and 129.59 eV, attributing to the P 2p 3/2 and P2p 1/2 species, respectively, together with the signature peak centered at 133.04 eV allocated to the P−O species due to the partial oxidation of the material surface [53–54] . Interestingly, the peaks of P 2p for Ni 3 P/Ni/VN@NC were shifted towards higher binding energy in comparison to Ni 3 P/Ni@NC, signifying that the P site behaved as an electron donor.…”
Section: Resultsmentioning
confidence: 94%
“…This demonstrated that the Ni site exerted electron donor properties and the metal Ni could act as a bridge for electron transfer between Ni 3 P and VN. Additionally, from the P 2p spectrum presented in Figure 3d, the P 2p of Ni 3 P/Ni/VN@NC could be distinguished by the featured peaks located at 128.48 and 129.59 eV, attributing to the P 2p 3/2 and P2p 1/2 species, respectively, together with the signature peak centered at 133.04 eV allocated to the P−O species due to the partial oxidation of the material surface [53–54] . Interestingly, the peaks of P 2p for Ni 3 P/Ni/VN@NC were shifted towards higher binding energy in comparison to Ni 3 P/Ni@NC, signifying that the P site behaved as an electron donor.…”
Section: Resultsmentioning
confidence: 94%
“…The overall OER mechanism is shown in Equation 9. [ 57 ] The CoNiO heterostructures with oxygen vacancies and electron deficient sites in the interface endow a large number of active sites for OER. The N‐CNF presents a higher density of states near the Fermi level that alters the electron density in the carbon matrix.…”
Section: Resultsmentioning
confidence: 99%
“…Easier water dissociation is promoted by synergistic effects at the interfaces. The charge transfer induced from the interfaces enables weakened reactant adsorption, hence preventing surface poisoning from the bonded reactants ( Janani et al, 2022 ; Surendran et al, 2022 ), resulting in easier hydrogen adsorption and desorption.…”
Section: Current Progress On Mixed Metal Oxide Electrocatalysts For T...mentioning
confidence: 99%